Hereditabilidad del tenor de prolina en hojas túrgidas y deshidratadas de frijol (Phaseolus vulgaris L.) - Menosso, O.G; Vieira, C; Bragarena, A; Silva, J.C (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
To determine the inheritance of free proline accumulation in the leaves of beans (Phaseolus vulgaris L), the cv Manteigao Fosco 11° (with a high content of proline) was crossed with the cv. Rico 23 (with a low content). Tests were conducted on parental, F1, F2 and backcross progenies. Data obtained from turgid leaves indicated that low content of free proline is partially dominant, and that approximately 4 genes are involved in the determination of this character. Broad sense heritability was estimated as 65.9% and heritability in the narrow sense as 51.7%. Data obtained from dehydrated leaves also indicated that low content of free proline is partially dominant. In this case, broad sense heritability was estimated as 84.5%.